Implementasi Pembelajaran Interaktif Menggunakan Gamifikasi Berbasis Kuis Digital dalam Meningkatkan Literasi Budaya pada Siswa Sekolah Dasar - Syifa’ur Rahmah; Feri Tirtoni (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
Cultural diversity in Indonesia is a wealth of the nation that must be understood and appreciated by the younger generation. However, the low cultural literacy of elementary school students is a challenge in learning. The study was conducted to see the effect of interactive learning based on gamification of digital quizzes on improving students' cultural literacy. This study uses a quantitative approach with a pre-experiment design of one group, namely the design of a onegroup pretestposttest with a sample of 23 students of class V who were selected through purposive sampling techniques at SDN Tawangsari III. Data collection was in the form of a multiple-choice test that was used to evaluate students' understanding before and after being treated. The results of the analysis showed that the posttest score  had increased significantly compared to the pretest  score with a value of t = 6.89 and p < 0.001, which shows that gamification has an effect on improving cultural literacy. This research proves that gamification-based learning of digital quizzes can increase students' activeness and strengthen their understanding of Indonesia's cultural diversity. Thus, the application of gamification has the potential to be an innovative approach in the learning process of social and cultural subjects at the elementary school level.